Multiple Re-entry Closures After TEVAR for Ruptured Chronic Post-dissection Thoraco-abdominal Aortic Aneurysm - R. Kinoshita; F. Ganaha; J. Ito; N. Ohyama; N. Abe; T. Yamazato; H. Munakata; K. Mabuni; T. Kugai (EJVES Short Reports, 2018)
Introduction: Although thoracic endovascular aortic repair (TEVAR) has become a promising treatment for complicated acute type B dissection, its role in treating chronic post-dissection thoraco-abdominal aortic aneurysm (TAA) is still limited owing to persistent retrograde flow into the false lumen (FL) through abdominal or iliac re-entry tears. Report: A case of chronic post-dissection TAA treatment, in which a dilated descending FL ruptured into the left thorax, is described. The primary entry tear was closed by emergency TEVAR and multiple abdominal re-entries were closed by EVAR. In addition, major re-entries at the detached right renal artery and iliac bifurcation were closed using covered stents. To close re-entries as far as possible, EVAR was carried out using the chimney technique, and additional aortic extenders were placed above the coeliac artery. A few re-entries remained, but complete FL thrombosis of the rupture site was achieved. Follow-up computed tomography showed significant shrinkage of the FL. Discussion: In treating post-dissection TAA, entry closure by TEVAR is sometimes insufficient, owing to persistent retrograde flow into the FL from abdominal or iliac re-entries. Adjunctive techniques are needed to close these distal re-entries to obtain complete FL exclusion, especially in rupture cases. Recently, encouraging results of complete coverage of the thoraco-abdominal aorta with fenestrated or branched endografts have been reported; however, the widespread employment of such techniques appears to be limited owing to technical difficulties. The present method with multiple re-entry closures using off the shelf and immediately available devices is an alternative for the endovascular treatment of post-dissection TAA, especially in the emergency setting. Keywords: Aortic dissection, Ruptured aortic aneurysm, Post-dissection thoracoabdominal aortic aneurysm, Endovascular aortic repair, Reentry closure, Endovascular procedures